Chronic poverty: issues, problems and challenges - International Conference on Challenges of Chronic Poverty in India (2008 : Centre for the Study of Social Systems, Jawaharlal Nehru University, New Delhi); Das, Ashish Kumar; Das, Sarada Prasanna; Kumar, Anand (New Delhi: Vitasta, 2017)
Contributed articles presented at the International Conference on Challenges of Chronic Poverty in India from October 1-3, 2008 at Jawaharlal Nehru University, New Delhi.
Includes bibliographical references and index
Keywords: Poverty -- India -- Congresses; Poverty -- Government policy -- India -- Congresses